Comparative Analysis of the Complete Chloroplast Genomes of Nine Paphiopedilum Species - Sun, Yin; Zou, Peishan; Jiang, Nannan; Fang, Yifu; Liu, Guofeng (Frontiers in Genetics, 2022)
Paphiopedilum is known as “lady’s or Venus” slipper orchids due to its prominent shoe-shaped labellum, with high ornamental value. Phylogenetic relationships among some species in Paphiopedilum genus cannot be effectively determined by morphological features alone or through the analysis of nuclear or chloroplast DNA fragments. In order to provide aid in understanding the evolutionary and phylogenetic relationship in Paphiopedilum at chloroplast (cp) genome-scale level, the complete cp genomes of six Paphiopedilum species were newly sequenced in this study, and three other published cp genome sequences of Paphiopedilum were included in the comparative analyses. The cp genomes of the six Paphiopedilum species ranged from 154,908 bp (P. hirsutissimum) to 161,300 bp (P. victoria-mariae) in size, all constituting four-part annular structures. Analyses of the nucleotide substitutions, insertions/deletions, and simple sequence repeats in the cp genomes were conducted. Ten highly variable regions that could serve as potential DNA barcodes or phylogenetic markers for this diverse genus were identified. Sequence variations in the non-coding regions were greater than that in the conserved protein-coding regions, as well as in the large single copy (LSC) and small single copy (SSC) regions than in the inverted repeat (IR) regions. Phylogenetic analysis revealed that all Paphiopedilum species clustered in one monophyletic clade in the Cypripedioideae subfamily and then subdivided into seven smaller branches corresponding to different subgenus or sections of the genus, with high bootstrap supports, indicate that cp genome sequencing can be an effective means in resolving the complex relationship in Paphiopedilum.